2002
DOI: 10.1053/joca.2001.0509
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of infiltrating T cells and Th1/Th2-type cytokines in the synovium of patients with osteoarthritis

Abstract: These observations suggest that Th1 cells predominate in the synovium of patients with OA, which clearly indicates that immune regulation occurs and may play critical roles in inflammation and cartilage destruction in patients with OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 12 publications
8
101
1
1
Order By: Relevance
“…However, we found insignificant difference in IL-6, INF-gamma in LLLT group compared to Lev group. Supporting our results, a previous study reported the involvement IFN-γ in the course of inflammation and cartilage damage in OA [21]. Another study by Nasonova et al showed that anti-INF gamma was superior to anti-TNF-alpha in treatment of rheumatoid arthritis [22], [23].…”
Section: Effects Of Ultrasound Versus Low Level Laser Therapy In Levosupporting
confidence: 90%
“…However, we found insignificant difference in IL-6, INF-gamma in LLLT group compared to Lev group. Supporting our results, a previous study reported the involvement IFN-γ in the course of inflammation and cartilage damage in OA [21]. Another study by Nasonova et al showed that anti-INF gamma was superior to anti-TNF-alpha in treatment of rheumatoid arthritis [22], [23].…”
Section: Effects Of Ultrasound Versus Low Level Laser Therapy In Levosupporting
confidence: 90%
“…Here we present the evidence, that only classically activated or M 1 macrophages are able to produce YKL-39 and that in response to IFN-γ and LPS stimulation undifferentiated monocytes were able to produce YKL-39. It has been shown that Th1 cells predominate in the synovium of patients with OA [38]. Consequently, IFN-γ which is one of the prevailing cytokine in OA tissues is able to induce the production of YKL-39 by monocyte-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-g was detected by means of immunohistochemistry (IHC) 26,57,63 . The cellular origin of IFN-g remains unclear.…”
Section: Cytokines Detected In Oa Stmentioning
confidence: 99%
“…Neutrophils were almost never found 21,34,35,44,48,62 . Overall OA ST contained fewer number of inflammatory cells than RA ST 25,30,36,37,44,45,56,57,63,65,68,69,71,75,78 , but more than normal control ST 25,34,44,45,50,51,55,57,59,61e63,65,67,70,71,75,78 .…”
mentioning
confidence: 92%